Is Biologic Therapy an Effective Tool for Achieving Remission in Severe Asthma? A Retrospective Study in Central Romania - Corina Mărginean; Dragoș Huțanu; Mara Andreea Vultur; Hédi-Katalin Sárközi; Edith-Simona Ianoși; Maria Beatrice Ianoși; Andreea Safta; Gabriela Jimborean; Corina Eugenia Budin (Life, 2025)
Background: Severe asthma, which is characterized by persistent symptoms despite standard therapies, presents a significant clinical challenge. Biologic therapies targeting specific inflammatory pathways offer a potential avenue for achieving disease remission. This retrospective study evaluates the effectiveness of biologic therapies in achieving remission in severe asthma within a central Romanian cohort. Methods: Forty-eight patients with severe asthma treated with omalizumab, benralizumab, or dupilumab (2020–2025) were assessed. Clinical remission was defined using ACT scores, exacerbation frequency, corticosteroid use, and FEV1. Biological remission was determined using FeNO and eosinophil levels. Statistical analysis was performed to compare treatment outcomes. Results: At 12 months, 75% of patients achieved biological remission, and 75% reached clinical remission criteria. Significant improvements were observed in FEV1 (p < 0.001), eosinophil counts (p < 0.001), and ACT scores (p < 0.001). Complete remission, encompassing clinical, biological, and functional normalization, was observed in 54.2% of patients. Conclusion: Biologic therapies demonstrate promise in inducing comprehensive remission in severe asthma, supporting their role in improving disease control and lung function. Further research with larger cohorts is warranted.